"FOR THE BENEFIT OF YOUNG WOMEN GOING INTO SERVICE": LATE EIGHTEENTH-CENTURY PROTO-YOUNG ADULT NOVELS FOR LABOURING-CLASS GIRLS. Issue 1 (2nd January 2016) - Kittredge, Katharine
ABSTRACT: At the end of the long eighteenth century, British female social reformers wrote didactic works of fiction for a labouring-class audience which encouraged their readers to preserve the social distinctions between the classes and exhibit honest and diligent work habits. Among these texts are works specifically designated for labouring-class girls who are leaving school or home to enter the workforce. These works follow the format of modern Young Adult novels in their structure, narrative devices and optimistic outlook. They revolve around young women who must learn to solve problems on their own, without adult help. These works are short, utilize either extensive dialogue or first-person narration, and emphasize peer relationships. Although there are some stories which feature dramatic punishments for misdeeds, for the most part, these works have an optimistic tone and convey a reassuring message about young people's abilities to overcome early missteps and to adapt successfully to the adult world. Taken together, these texts provide a view of a phase of women's lives that has received little attention in previous literary and historical studies, as well as insight into an early incarnation of a genre that has recently risen to prominence.